Evaluation of the Rationality of Antibiotic Drugs in Patients with ISPA (Acute Respiratory Tract Infection) at Dr. Moewardi Regional General Hospital (RSUD) Surakarta - Nurchaina Aprilia Dewi; Kharisma Jayak Pratama; Tatiana Siska Wardani (CV. AFDIFAL MAJU BERKAH, 2026)
Acute Respiratory Tract Infection (ARTI) remains a major infectious disease in Indonesia, significantly affected by inappropriate antibiotic utilization, potentially increasing bacterial resistance. This study aims to evaluate the rationality of antibiotic use among ARTI inpatients at Dr. Moewardi General Hospital, Surakarta. Utilizing a quantitative, retrospective descriptive design, all medical records of ARTI inpatients from 2023 to 2025 meeting the inclusion criteria were included as samples (total sampling). Data were collected using structured forms and processed using Microsoft Office and IBM SPSS Statistics 20; analysis was performed descriptively following Gyssens' criteria. The study found that although most patients received correct antibiotics with respect to indication (94.7%), drug type (94.7%), dose (100%), and timing (100%), only 34.2% received antibiotics for the appropriate duration. Rational antibiotic use by Gyssens' method was found in only 34.2% of cases. These findings highlight the high rate of duration errors and emphasize routine audits and educational interventions. It is concluded that, despite strengths in dosage and selection, duration of antibiotic use remains a challenge for rational therapy.